Estimating the Knowledge-Capital Model of the Multinational Enterprise: Reply - Carr, David L; Markusen, James R; Maskus, Keith E (American Economic Review, 2003)
Estimating the Knowledge-Capital Model of the Multinational Enterprise: Reply by David L. Carr, James R. Markusen and Keith E. Maskus. Published in volume 93, issue 3, pages 995-1001 of American Economic Review, June 2003